2013
DOI: 10.1371/journal.pone.0058566
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Characteristics of Ubiquitin-Specific Peptidase 46-Deficient Mice

Abstract: We have previously identified Usp46, which encodes for ubiquitin-specific peptidase 46, as a quantitative trait gene affecting the immobility time of mice in the tail suspension test (TST) and forced swimming test. The mutation that we identified was a 3-bp deletion coding for lysine (Lys 92), and mice with this mutation (MT mice), as well as Usp46 KO mice exhibited shorter TST immobility times. Behavioral pharmacology suggests that the gamma aminobutyric acid A (GABAA) receptor is involved in regulating TST i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…Our network analysis is carried out on brains of ethanol-naive animals, and thus, generates insight into the systems that are associated with the predisposition to consume alcohol. The mutation or knockout of one protein associated with these systems, ubiquitin-specific peptidase 46 (Usp 46), has very recently been demonstrated to reduce ethanol preference in mice [87]. This study validates the involvement of the system related to protein processing and protein degradation as an in vivo modulator of the phenotype of alcohol consumption.…”
Section: Discussionsupporting
confidence: 52%
“…Our network analysis is carried out on brains of ethanol-naive animals, and thus, generates insight into the systems that are associated with the predisposition to consume alcohol. The mutation or knockout of one protein associated with these systems, ubiquitin-specific peptidase 46 (Usp 46), has very recently been demonstrated to reduce ethanol preference in mice [87]. This study validates the involvement of the system related to protein processing and protein degradation as an in vivo modulator of the phenotype of alcohol consumption.…”
Section: Discussionsupporting
confidence: 52%
“…Due to these important functions, USP1 is considered a major possible drug target (Liang et al, 2014). USP46 plays important roles in neurobiology, as a small deletion mutation in USP46 leads to neurological effects in mice, including anxiety and changes in learning and memory (Imai et al, 2013, Zhang et al, 2011). The molecular basis for these effects is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Combat Exposure Scale (CES), a self-reporting scale, was administered for measuring the level of wartime traumatic stressors experienced by the combatants [30]. The total CES scores were divided into ve categories of combat exposure: light (1-8), lightmoderate (9-16), moderate (17)(18)(19)(20)(21)(22)(23)(24), moderate-heavy (25)(26)(27)(28)(29)(30)(31)(32), and heavy (33)(34)(35)(36)(37)(38)(39)(40)(41). The Alcohol Use Disorders Identi cation Test (AUDIT) was also used to assess hazardous and harmful alcohol use [31].…”
Section: Methodsmentioning
confidence: 99%
“…In animal studies, USP46 has been implicated in regulating the GABAergic system and Alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) glutamatergic system, which are important for inter-neuronal communication and higher brain functions such as learning and memory [21][22][23][24]. Notably, Ebihara and colleagues reported that Usp46 knockout mice display shortened immobility times in the tail suspension test [24] and long-term memory de cits in the object recognition test [25]. Furthermore, in humans, a genetic association between a haplotype of USP46 and major depression was reported in a Japanese population [26].…”
Section: Introductionmentioning
confidence: 99%